KRIMINALITAS PRAKTIK NIKAH SIRI DAN POLIGAMI DI INDONESIA - Defel Fakhyadi (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Siri marriage and polygamy are forms of marriage that are permitted in Islamic law, these actions are categorized as against the law if they are not carried out according to applicable laws. Criminality in civil law in the form of violations can occur if the aggrieved party files a lawsuit in court over the case of siri marriage and polygamy that does not have a license because every marriage must be recorded. The state regulates the registration of marriages and polygamy in order to create marriage administration so that it does not cause harm to the married couple when divorce, maintenance and inheritance rights occur. This literature-based study wants to reveal the criminality in marriage based on the social reality of society in Indonesia. This type of research is descriptive qualitative based on literature research with data analysis through a descriptive critical analysis approach so as to produce a comprehensive understanding of legal marriage in Islamic law. This study concludes that the behavior of siri marriage and polygamy has a major impact on the order of family law in Indonesia so that the government regulates the administration of marriage by considering the side of kemashlahatan even though it sometimes has an understanding debate with traditionalist-centric fiqh thinking. The provision of sanctions against the criminal behavior of nikah siri and polygamy is a sanction against criminal offenders so that it is more social in nature so that the creation of responsive family law for the realization of a sakinah family, mawaddah warahmah